PENGARUH PEMBERIAN EKSTRAK ETANOL DAN KLOROFORM DAUN SIRSAK TERHADAP KOLESTEROL TOTAL DAN TRIGLISERIDA PADA TIKUS YANG DIINDUKSI ALOKSAN - Deni Firmansyah; Moch Saiful Bachri; Nurkhasanah Nurkhasanah (Universitas Ahmad Dahlan, 2016)
Annona muricata plant is a medicinal plant using by research and drug for human healthy including diabetes mellitus. This research aimed to determine the effect of ethanol extract and chloroform extract of the sirsak leaf as antidiabetes mellitus. This research was conducted in 9 groups of male Wistar rats consisting of 5 rats per group, consisting of normal control, alloxan control, glibenclamide control dose of 10 mg/Kg BW, group of ethanol extract sirsak leaf dose of 50 mg/Kg BW; 100 mg/Kg BW; 200 mg/Kg BW, and group of chloroform extract sirsak leaf dose of 50 mg/kg BW; 100 mg/Kg BW; 250 mg/Kg BW. Tests carried out for 2 weeks. It also conducted assays of total flavonoids and histopathological tests of pancreatic Î² cells. Results of this research showed that the ethanol extract ofÂ sirsak leaves dose of 200 mg/Kg BW has activity in decreasing blood glucose levels better than any other group. Results of the ethanol extract and chloroform extract all doses except the ethanol extract treatment group dose of 200 mg/kg BW and 100 mg/kg BW after a 14-day look is still high triglyceride levels and decrease in total cholesterol (TC) were seen in all group Ethanol extract dose of 200 mg / kgBWÂ has a good potential to reduce levels of triglycerides and total cholesterol. The conclusion of this research is the ethanol extract of sirsak leaf have activity antidiabetic mellitusand decreased total cholesterol.Â